2009
DOI: 10.1016/j.ejcnurse.2008.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life after Coronary Artery Bypass Graft Surgery in the Elderly

Abstract: A high proportion of the patients experienced improvement while a substantial number had exacerbations related to self confidence and dependence to others. An important step to improve this situation might be through the institution of a structured multi-disciplinary rehabilitation program with focus on emotional support, information giving and education to elderly CABG patients and their significant others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 66 publications
2
26
0
Order By: Relevance
“…In this study, in order to evaluate the quality of life, the MacNew questionnaire was used and the quality of life of patients was investigated before the surgery, four months after the surgery and one year later. The results of this study showed that the quality of life of patients increased significantly four months after the CABG surgery and this improvement was observed with lower degrees for one year after [27]. Wissler et al found that the quality of life of patients improved after rehabilitation [28].…”
Section: Discussionmentioning
confidence: 57%
“…In this study, in order to evaluate the quality of life, the MacNew questionnaire was used and the quality of life of patients was investigated before the surgery, four months after the surgery and one year later. The results of this study showed that the quality of life of patients increased significantly four months after the CABG surgery and this improvement was observed with lower degrees for one year after [27]. Wissler et al found that the quality of life of patients improved after rehabilitation [28].…”
Section: Discussionmentioning
confidence: 57%
“…In addition, McCormick (2001) found that the least frequent symptoms were anorexia and irregular heart rate. While in contrast to these results, more than one third of CABG patients post-discharge reported AF as the most common complication after surgery (Hogue et al, 2005;Merkouris et al, 2009). …”
Section: Discussionmentioning
confidence: 92%
“…Escalating medical costs, limitation of resources and the necessity to provide cost-effective medical care have increased the need for assessment of the outcomes of any intervention or method of treatment (Merkouris et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…13 This study revealed that the QoL was higher in both men and women after CABG, which is supported by published literature. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] It was interesting to note that higher scores were seen in all domains of QoL in the post-CABG group, except the socio-economic domain. These differences may be attributed to multiple factors, eg.…”
Section: Discussion Pre and Post-operative Qolmentioning
confidence: 99%